Environmental Engineering and Computer Application: Proceedings of the 2014 International Conference on Environmental Engineering and Computer Application (ICEECA 2014), Hong Kong, 25-26 December 2014 - Chan, Kennis (CRC Press, 2015)
The awareness of environment protection is a great achievement of humans; an expression of self-awareness. Even though the idea of living while protecting the environment is not new, it has never been so widely and deeply practiced by any nations in history like it is today. From the late 90s in the last century, the surprisingly fast development of computer science has brought many new technologies which have already been applied in countless fields like manufacturing, military, aerospace and pharmacy. Now, another important field-the environment engineering is welcoming the introduction of these technologies. The 2014 International Conference on Environment Engineering and Computer Application (ICEECA2014) has brought together researchers in environment fields and in computer fields, and encourages to find potential use for computer technologies in environment protection fields.ICEECA2014, successfully held on December 25 26, 2014 in Hong Kong, is a grand gathering attended by experts and researchers from all around the world. The participants at ICEECA2014 have generously shared their inspiring work and exchanged their innovative ideas of how to help the environmental sciences benefit from the development of computer technology and vice versa. This book, as one of the many accomplishments for ICEECA2014, is the cooperative work of many people and organizations. It comprises all the papers accepted by ICEECA2014. These papers are accepted after careful review and they will prove to be valuable  for the future.Papers in this book are put under several different chapters including subjects like environmental engineering, remote sensing, GIS and application, graphic and image processing and computational science and application.